Possible Benefit of Angiotensin II Receptor Blockers in COVID-19 Patients: A Case Series - Lee, Su Jin; Kim, Taehwa; Cho, Woo Hyun; Jeon, Doosoo; Lim, Seungjin (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Introduction. Dysfunction in the renin-angiotensin-aldosterone system (RAAS) has been observed in patients with coronavirus disease 2019 (COVID-19). It is presumed that the effect of reducing interleukin-6 (IL-6) levels by angiotensin II receptor blockers (ARBs) by RAAS modulation. We investigated changes in angiotensin II and IL-6 levels in four COVID-19 patients treated with ARBs. Case Presentation. Cases 1 and 2 were who had not received ARBs before and were newly administered ARBs. Case 3 restarted ARBs after discontinuation for 7 days, and case 4 received an increased dose of ARBs. The mean in angiotensin II levels (607.5 pg/mL, range: 488–850 pg/mL, reference range<100 pg/mL), C-reactive protein (CRP) (10.58 mg/dL, range 4.45-18.05 mg/dL), and IL-6 (55.78 pg/mL, range: 12.86–144.82 pg/mL, reference range<7 pg/mL) was observed at the admission in all patients. Upon clinical improvement, the mean decrease in CRP (1.02 mg/dL, range 0.06-3.78 mg/dL) and IL-6 (5.63 pg/mL, range 0.17-20.87 pg/mL) was observed in all patients. Conversely, angiotensin II levels gradually increased. Conclusion. This report supports the potential benefit of ARBs to improve the clinical outcomes of COVID-19 patients by controlling RAAS dysfunction.